Pressure sensing behaviour of sodium bismuth titanate ceramics - Mohammad Hafizuddin Haji Jumali,; Mohd Riduan Mt Said,; Ngoi, Yung Wee; Muhammad Yahaya, (Universiti Kebangsaan Malaysia, 2010)
A study to determine the microstructure and pressure sensing behaviour of Na0.45Bi0.55TiO3 (NBT) as lead-free ceramics has been conducted. NBT ceramics were prepared using the solid state reaction technique from stoichiometric mixture of Na2CO3, Bi2O3 and TiO2 powders. The mixture was sintered at three different temperatures namely 1100 oC, 1200 oC, 1300 oC for 12 hours. After sintering, the NBT powders were ground and pressed into pellet with 13 mm diameter and subsequently heated at 700 oC for 2 hours. Microstructure and morphology of the samples were determined using XRD and SEM, respectively. Customized pressure chamber using pneumatic load was employed for pressure sensing behaviour of the samples. X-ray diffraction analysis revealed that all samples consist of more than 70% of polycrystalline, rhombohedral NBT phase, with bismuth titanate, Bi2Ti2O7 (BTO) as the secondary phase. The increment in sintering temperature has resulted in the formation of higher NBT content in the sample. SEM micrographs showed that grain size and bulk density of the samples increased with the increment of sintering temperature. Pressure sensing test showed that all samples were responsive toward pressure variations only when initial voltage was applied to the ceramics. Based on density, stability and repeatability in pressure sensing behavior, NBT ceramic sintered at 1200 oC was the best ceramic with great potential as lead free pressure sensing material.